The application of pringle manoeuvre, type three liver mobilisation, full thickness diaphragmatic resection with primary closure technique and peritonectomy in the management of advanced ovarian malignancy - Sarah Louise Smyth; Hooman Soleymani Majd (Obstetrics & Gynecology Science, 2023)
Objective We present an educational technique for the safe completion of complete cytoreduction of diaphragmatic disease for the management of advanced ovarian malignancy. Methods We demonstrated these steps with attention to anatomical landmarks and surgical approaches, considering intraoperative and postoperative morbidity and mortality. Results We present the case of a 49-year-old female patient diagnosed with suspected stage 3C ovarian malignancy following diagnostic laparoscopy. We demonstrate the surgical application of the Pringle manoeuvre, type 3 liver mobilisation, and full-thickness diaphragmatic resection. This was completed with a primary closure technique, with integrity ensured through the performance of an air test and Valsalva manoeuvre. Final histology confirmed a serous borderline tumour with invasive implants within a port site nodule (stage 4A). Conclusion This technique affirms the essential skills in gynaecological oncology training and details a challenging case requiring advanced surgical skills and knowledge, with specific consideration for intraoperative multidisciplinary decision-making.